2017
DOI: 10.1038/s41598-017-02324-9
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance PVC Gel for Adaptive Micro-Lenses with Variable Focal Length

Abstract: This paper presents a bio-inspired adaptive micro-lens with electrically tunable focus made of non-ionic high-molecular-weight polyvinyl chloride (PVC) gel. The optical device mimics the design of the crystalline lens and ciliary muscle of the human eye. It consists of a plano-convex PVC gel micro-lens on Indium Tin Oxide (ITO) glass, confined with an annular electrode operating as an artificial ciliary muscle. Upon electrical activation, the electroactive adhesive force of the PVC gel is exerted on the annula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 26 publications
1
55
0
Order By: Relevance
“…The given results showed that with the addition of ionic liquid contents, the stress and strain were enhanced and directed that these gels are highly flexible and suitable for the actuator applications. 25…”
Section: Mechanical Properties Of Plasticized Pvc and Pvc/il Gelsmentioning
confidence: 99%
“…The given results showed that with the addition of ionic liquid contents, the stress and strain were enhanced and directed that these gels are highly flexible and suitable for the actuator applications. 25…”
Section: Mechanical Properties Of Plasticized Pvc and Pvc/il Gelsmentioning
confidence: 99%
“…PVC gel actuators exhibit large amounts of deformation and a wide range of motions that can be achieved by creating appropriate boundary conditions for the actuators, allowing the creeping motion to be utilized for different mechanisms (bending, contracting, etc.) 19 .…”
Section: Introductionmentioning
confidence: 99%
“…At that time, the plasticizers in the high-molecular-weight PVC gel can accelerate the movement of PVC chains toward an anode. Because there are many more PVC chains near an anode in the high-molecular-weight PVC gel than in the lower-molecular-weight PVC gel, more PVC chains can be influenced by applied electric field [27]. For these reasons, we expect that the molecular weight of the PVC will affect the deformation of the PVC gel-based bending actuator and its response time.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a PVC with high molecular weight has denser entanglement and more physical crosslinking, so excess plasticizer can be retained in the PVC chain matrix. Previously, we investigated the effect of the molecular weight of the PVC resin on the electroactive performance of plasticized PVC gels [27]. Because a high-molecular-weight PVC can accept more plasticizer, the performance of PVC gels based on high-molecular-weight PVC resin increases.…”
Section: Introductionmentioning
confidence: 99%